2012
DOI: 10.1161/circresaha.111.263715
|View full text |Cite
|
Sign up to set email alerts
|

A Cell-Based Phenotypic Assay to Identify Cardioprotective Agents

Abstract: Rationale Tissue ischemia/reperfusion (IR) injury underlies several leading causes of death such as heart-attack and stroke. The lack of clinical therapies for IR injury may be partly due to the difficulty of adapting IR injury models to high-throughput screening (HTS). Objective To develop a model of IR injury that is both physiologically relevant and amenable to HTS. Methods and Results A micro-plate based respirometry apparatus was used. Controlling gas flow in the plate head space, coupled with the ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 60 publications
0
23
0
Order By: Relevance
“…Cellular glycolysis was determined by measuring the ECAR in NRCMs using a Seahorse Bioscience XF24 extracellular flux analyzer (Billerica) as described previously (41). An increased oxygen consumption rate (OCR) immediately following the addition of palmitate substrate to the cells was used as an indicator for FAO in the XF24 Analyzer.…”
Section: The Journal Of Clinical Investigationmentioning
confidence: 99%
“…Cellular glycolysis was determined by measuring the ECAR in NRCMs using a Seahorse Bioscience XF24 extracellular flux analyzer (Billerica) as described previously (41). An increased oxygen consumption rate (OCR) immediately following the addition of palmitate substrate to the cells was used as an indicator for FAO in the XF24 Analyzer.…”
Section: The Journal Of Clinical Investigationmentioning
confidence: 99%
“…H9c2 myoblasts, derived from embryonic rat ventricle, were an excellent model system in which to directly test the effects of V 1A R signaling during in vitro stress, as they express cardiac and skeletal isoforms of L-type Ca 21 channels, sarcolemmal ATPase splice variants characteristic of a normal heart and endogenous V 1A R, which respond to AVP with typical Ga q protein-coupled receptor responses (Hescheler et al, 1991;Sipido and Marban, 1991;Hammes et al, 1994;Tran et al, 1995;Reilly et al, 1998;Chen and Chen, 1999;Guo et al, 2012). During the development of the H/R model, we initially found that H/R increased caspase 3/7 activity and decreased cell viability with enhanced robustness over normoxic conditions only under serum-free conditions, whereas the presence of fetal bovine serum protected the cells.…”
Section: Avp Protects H9c2mentioning
confidence: 99%
“…air) with subsequent short-term exposure to different O 2 concentrations during various treatments (drugs, photodynamic irradiation, hypoxia-reperfusion, etc.) [4,5,7,[9][10][11][12]. The consequences of long-term exposure to hyperoxic or physioxic environments on the subsequent cell killing effects of cancer treatments (e.g.…”
Section: Introductionmentioning
confidence: 99%